AUDIT DIGITALIZATION BY AUDIT TOOL AND LINKED ARCHIVE SYSTEMS (ATLAS) IN SUPPORTING FINANCIAL REPORT AUDIT - Yusnita, Erni; Jaudah, Jihan Fadhilah Hang; Melisa, Melisa; Winarti, Tri; Fajaria, Ulfa; Maulana, Muhammad Ilham; Ikhsan, Syarbini; Espa, Vitriyan (Jurnal KIAFE, 2023)
The audit of financial statements is one of the aspects that is influenced by the presence of Computer-Assisted Audit Techniques at the Public Accounting Firm as audit work papers, making it easier for auditors to provide their services. The Audit Tool and Linked Archive System (ATLAS) application assists auditors in the application of Auditing Standards and Public Accountant Professional Standards. The purpose of this study is to determine the auditor's perspective at KAP Syarbini Ikhsan on audit digitization through the ATLAS application in supporting the financial statement audit process. The method in this research is descriptive qualitative, which is based on theoretical studies, results from previous studies, observations, and interviews, which are then collected, analyzed, and concluded. The results of the research show that the ATLAS application acts as a tool for the Ministry of Finance to seek uniform reporting for all public accounting firms in Indonesia. Other results also show that KAP Syarbini Ikhsan has been slowly implementing ATLAS since 2019 to support its financial report audit process, but this implementation has not been carried out optimally.